Chronic hepatitis without hepatic steatosis caused by citrin deficiency in a child. Issue 4 (18th August 2015) - Inui, Ayano; Hashimoto, Takuji; Sogo, Tsuyoshi; Komatsu, Haruki; Saheki, Takeyori; Fujisawa, Tomoo
Abstract : Citrin deficiency manifests as both neonatal intrahepatic cholestasis (NICCD) during early infancy and adult‐onset type II citrullinemia during adulthood. Hepatic steatosis is most frequently observed in patients with citrin deficiency. Thus, non‐alcoholic fatty liver disease that is unrelated to being overweight is considered one of the clinical features of citrin deficiency in children and adults. However, it remains unknown whether citrin deficiency is a cause of chronic hepatitis in the absence of fatty changes to the liver that occur during childhood. We encountered an 8‐year‐old girl who showed no clinical features of NICCD during infancy and had persistently elevated transaminase levels for several years. Liver biopsy showed widening of the portal tracts with intense mononuclear cell infiltration and mild fibrosis but no fatty changes. However, she had peculiar dietary habits similar to those that have been observed in many patients with citrin deficiency. In addition, a slightly elevated plasma citrulline level and a high pancreatic secretory trypsin inhibitor level were detected by blood examination, and she was diagnosed with citrin deficiency. Analysis of the SLC25A13 gene revealed the presence of the compound heterozygous mutations 851del4 and IVS13 + 1G > A. Thus, citrin deficiency should be included in the differential diagnosis of chronic hepatitis in children, even in the absence of hepatic steatosis.